THERMAL RESORTS OF EXTREMADURA AND ENGAGEMENT WITH CONSUMER IN FACEBOOK (SPAIN) - Coutinho-Pires dos Santos, Barbara; Filomena-Torres, Maria; Cunha, Carlos; Durán-Sánchez, Amador (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2016)
With the advent of social networks, the building of Engagement between consumers and brands surpassed the limits of off-line relationships, and became reflected on-line. Social networks became then an essential tool for consumers, whether as regards the decision to purchase, or the searching for information, a primary item for touristic activity. With the purpose of facilitating access to information on their products and services, the thermal resorts of the Autonomous Region of Extremadura, in Spain, have invested in Facebook pages. However, just the presence in said social network is not sufficient anymore, becoming necessary to interact with their users. In order to understand if such interaction between the Facebook pages of Extremadura Thermal Resorts and their consumers is being efficient or not, this work aims at measuring and comparing the Engagement level of each of those thermal resorts (in their official Facebook pages), through digital metrics defined as from literature review, with the purpose of assisting administrators in the elaboration of communication strategies that might increase interaction and the involvement of fans with their brands. As methodology, two analyses were also used: a digital metrics and a content analysis, carried out in the period considered of high season, between the months of June and October, and in which all-thermal resorts were in operation. It was observed that Extremadura thermal resorts, in their great majority, are using the Facebook tool adequately, facilitating communication with their potential clients.